Pengembangan Media Pembelajaran Interaktif Berbasis Canva yang Terintegrasi dengan Pembelajaran Berbasis Masalah untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas Lima dalam IPAS pada Topik Rantai Makanan - Hariyanto; Angga Dwi Purnomo; Kustiyowati (Jurnal Penelitian Pendidikan IPA, 2026)
The development of critical thinking skills has become an essential competence in 21st-century education, requiring learning processes that are meaningful and problem-oriented. However, science learning (IPAS) in elementary schools still tends to emphasize conceptual memorization, resulting in students’ critical thinking skills, particularly in ecosystem topics such as food chains, being insufficiently developed. This study aimed to develop and examine the effectiveness of Canva-based interactive media integrated with the Problem-Based Learning (PBL) model in improving fifth-grade students’ critical thinking skills. The study employed a Research and Development (R&D) approach using the ADDIE model, followed by an effectiveness test using a Pretest–Posttest Control Group design. The research participants consisted of 44 students, including 25 in the experimental group and 19 in the control group. Data were collected using a validated critical thinking test that assessed the indicators of interpretation, analysis, evaluation, and inference. Data analysis was conducted using a t-test and effect size calculation. The results indicate that the implementation of Canva-based interactive media through the PBL model had a significant positive effect on students’ critical thinking skills. The effect size value of 1.670 indicates a very high level of impact. These findings suggest that integrating interactive digital media with problem-based learning effectively enhances students’ active engagement and analytical abilities in IPAS learning.